2020
DOI: 10.21891/jeseh.656048
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Preservice Teachers’ Epistemological Beliefs, Knowledge Levels and Attitudes regarding Organ Transplantation and Donation

Abstract: In this study, preservice teachers' epistemological beliefs and attitude/knowledge level regarding organ transplantation and donation (OTD) are investigated according to such demographical variables as gender, department and grade level. Teachers play a fundamental role in providing information to children/adolescents and could influence their attitudes. Organ transplantation is a life-saving hope for many people around the world. But, shortage of organs for transplantation is essentially a universal problem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the contrary, the results of the study by Wolide et al indicated that male students had higher knowledge score ( 18 ). However, other studies did not confirm any significant relationship between gender and knowledge of participants about organ donation ( 17 , 24 – 26 ).…”
Section: Discussionmentioning
confidence: 80%
“…In the contrary, the results of the study by Wolide et al indicated that male students had higher knowledge score ( 18 ). However, other studies did not confirm any significant relationship between gender and knowledge of participants about organ donation ( 17 , 24 – 26 ).…”
Section: Discussionmentioning
confidence: 80%
“…It is widely believed in society that men, who are the "breadwinners", may be more reluctant to donate their organs compared to women, whose decision to donate is largely influenced by their parents, spouses or both. However, there are also studies that do not confirm the existence of any relationship between sex and the knowledge of organ donation [25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The present study used SST scenarios to investigate the PTs' written arguments. Studies in the literature have also used various SST scenarios, including genetically modified organisms (GMO), environmental pollution, climate change, and organ transplantation and organ donation, to investigate written argumentation levels of PTs (Soysal, 2012;Torun & Açıkgül-Fırat, 2020;Yalçın, 2018;Gürkan, 2018). Torun and Açıkgül Fırat (2020).…”
Section: Discussionmentioning
confidence: 99%